Analysis of Animal-Sourced Protein Food Demand Function in Household in East Java and East Nusa Tenggara - Nofal, Bahieddin; Suhartini, Suhartini; Fahriyah, Fahriyah (HABITAT, 2024)
The consumption of animal-sourced protein food in Indonesia is projected to continue increasing. However, current issues include low average consumption levels, a significant share of expenditure, and relatively high prices of some animal-sourced protein foods. This study analyzed the demand function for animal protein food consumption to identify the factors influencing household consumption and examined own-price elasticity, cross-price elasticity, and income elasticity. The analysis used SUSENAS consumption data, including household members, income, and food expenditure, and employed the QUAIDS model. The results showed that all variables were significant at the 1 percent level, implying that animal protein food commodities were influenced by household income, own-price, prices of other commodities, and socio-demographic factors (household size, age of household head, education level of household head, and region) in East Java and East Nusa Tenggara. The animal food commodity most sensitive to income changes in East Java was milk (1.409%), followed by meat (1.252%), and fish (1.214%) as luxury goods, and eggs (0.433%) as normal goods. The Marshallian (uncompensated) and Hicksian (compensated) own-price elasticities for all commodities in East Java and NTT were negative, indicating that the demand for animal protein food adhered to the law of demand. The Hicksian (compensated) cross-price elasticity values for other commodities in East Java and NTT were positive, suggesting that these commodities are substitutes for one another.